The role of communication contact in capitation implementation at public health centres in Denpasar - Ni Putu Purlimaningsih; I Ketut Suarjana; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2017)
care is the contact between the provider and the recipient (communication contact). Targets set regarding communication contacts are often not achieved which in turn results in consequent cuts in the capitation rates received by the public health centres (PHCs). The purpose of this research is to understand the implementation, inhibiting and enabling factors of supporting communication contact in the era of National Health Insurance (Jaminan Kesehatan Nasional/JKN). Methods: This study used a qualitative explorative design through in-depth interviews and focus group discussion (FGD) with 22 informants consisting of heads of PHCs, PHCs staff, Head of Denpasar Health Office, Head of Social Security Administering Agency (BPJS) Denpasar Branch and JKN members. This research was conducted at 11 PHCs in Denpasar City from April to July 2017. The informants were chosen purposively and the data were analysed thematically to explore aspects of implementation, the inhibiting and enabling factors of communication contact. Results: Communication contacts can be assessed both inside and outside the PHCs buildings. The inhibiting factor of communication contact implementation related to difference in understanding of the concept of PHCs working area, the absence of a standard operational procedure (SOP) for communication contact, heavy workload of PHCs service providers, lack of optimal means of supporting application of pcare convoluted and confusing information from BPJS, and lack of understanding from JKN enrolees on the particulars of the administration and desire for speedy service. Supporting factors are the availability of media, training and orientation for the implementing staff and the feedback from BPJS to PHCs staff. Driving factors are the effective authority of the PHCs head, commitment and motivation from government agencies and cross-sectoral support. Conclusions: Implementation of communication contact is influenced by both inhibiting and enabling factors, from the BPJS stakeholders and the members of the BPJS. Achieving the target of communication contact requires synergy of central government policy and BPJS managers.